Can Mindfulness Help to Predict Veterans' Mental Health Service Utilization?. Issue 4 (27th September 2019) - Barr, Nicholas; Kintzle, Sara
Abstract: Post–9/11 era military veterans are at high risk for posttraumatic stress disorder (PTSD) and depression, but less than half of veterans who screen positive for these disorders seek mental health treatment. Self-stigma of mental illness has emerged as a core barrier to mental health service use (MHSU) in this population. Mindfulness is associated with attention control, nonjudgment, and reduced self-stigma in civilians, but associations between PTSD and depression, mindfulness, self-stigma, and MHSU have never been investigated in military veterans. The present study used a logistic regression modeling strategy to investigate main and interaction effects for PTSD, depression, mindfulness, and self-stigma on MHSU. Study findings demonstrated a positive main effect for PTSD and negative main effects for mindfulness and self-stigma on MHSU, and a positive interaction effect for mindfulness and PTSD on MHSU. Findings suggest that more mindful individuals with PTSD symptoms are more likely to seek mental health services, whereas less mindful individuals with PTSD symptoms are less likely to seek treatment. More research into the potential for mindfulness to enhance MHSU outcomes for military veterans appears warranted.